Is the Concept of Umorismo Modern? - Roić, Sanja (Array, 2008)
Pirandello’ s Saggio su l’ Umorismo is still arousing a lot of interest among literary theoreticians either for its contents of for its reception. At the historical moment of its writing (it was in 1907 /1908 and Pirandello was teaching at the teacher-training college in Rome), the concept of humour was theorized per negationem through the so-called “ avvertimento del contrario” and then “ sentimento del contrario” . On this occasion I’ ll try to place emphasis upon some explicit and implicit points of reference that Pirandello established in that context about certain German theories. I would also like to find out whether at the time that concept had been thought of as modern and, referring to U. Eco’ s theories, to M. Kundera’ s narrative solutions and to R. Benigni’ s creativity at set, to verify to what extent the concept of umorismo has been vital and productive in postmodernism.